Critical analysis of the Armed Forces Covenant Fund Trust Aged Veterans Fund. Issue 1 (31st March 2021) - Di Lemma, Lisa C G; Finnegan, A; Howe, S
Abstract : Background: Relatively little research is available regarding the specific needs of older military veterans and the services introduced to support them. In 2016, the Armed Forces Covenant Fund Trust launched the Aged Veterans Fund (AVF), to understand the impact that military service may have on ageing, and to support initiatives targeting their health and well-being. This fund was financed for 5 years and included 19 UK portfolio projects. Method: The paper presents a retrospective evaluation on the processes and impact of the AVF, with the intent of informing policy, educational services, service providers and stakeholders of the lessons learnt. The inclusion criteria was veterans and their families aged 65 years of age or over. In 2019, data were drawn from documentary evidence related to the programmes. Qualitative analysis were performed on 78 eligible sources and 10 themes were identified. Results: Programmes were rolled out via collaborative partnerships referrals, focusing on person-centred or skill-exchange approaches. Challenges were encountered, such as capacity and timelines issues. A limited amount of associated cost-savings was observed, even if examples of sustainability and high satisfaction were reported. Evidence was found of programmes boosting health and well-being outcomes, in raising awareness, and in positively impacting on clinical practice, such as re-admission rates. Conclusion: The AVF programmes were successful in their intent to provide support to older veterans and their families. The findings provide indicators of the next steps required for the support of ageing veterans. Further investigation of the cost-effectiveness of age-friendly veterans' services is needed.